2020
DOI: 10.1002/hbm.25162
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal complexity patterns of resting‐state bioelectrical activity explain fluid intelligence: Sex matters

Abstract: Neural complexity is thought to be associated with efficient information processing but the exact nature of this relation remains unclear. Here, the relationship of fluid intelligence (gf) with the resting‐state EEG (rsEEG) complexity over different timescales and different electrodes was investigated. A 6‐min rsEEG blocks of eyes open were analyzed. The results of 119 subjects (57 men, mean age = 22.85 ± 2.84 years) were examined using multivariate multiscale sample entropy (mMSE) that quantifies changes in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 138 publications
(216 reference statements)
6
27
0
Order By: Relevance
“…Sample entropy of frontocentral channels demonstrated non-significant negative associations with intelligence at finer timescales, while sample entropy of fronto-parietal channels at coarser time scales demonstrated non-significant tendencies towards positive associations. Together, the finding of lower entropy at finer time scales and tendencies towards higher entropy at coarser time scales to be associated with higher intelligence is in line with the findings of Dreszer et al (2020) suggesting differences in local (linked to entropy at finer time scales) versus global (as reflected by entropy at coarser time scales) aspects (Vakorin et al, 2011;McIntosh et al, 2014;Courtiol et al, 2016) of intelligence-related information processes. Interestingly, it has been shown that entropy at finer time scales increases while entropy at coarser time scales decreases with increasing age (McIntosh et al, 2014), which is in regard to our observations, plausible as fluid intelligence decreases with increasing age (Schaie, 1994;Salthouse, 2010;Ghisletta et al, 2012).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Sample entropy of frontocentral channels demonstrated non-significant negative associations with intelligence at finer timescales, while sample entropy of fronto-parietal channels at coarser time scales demonstrated non-significant tendencies towards positive associations. Together, the finding of lower entropy at finer time scales and tendencies towards higher entropy at coarser time scales to be associated with higher intelligence is in line with the findings of Dreszer et al (2020) suggesting differences in local (linked to entropy at finer time scales) versus global (as reflected by entropy at coarser time scales) aspects (Vakorin et al, 2011;McIntosh et al, 2014;Courtiol et al, 2016) of intelligence-related information processes. Interestingly, it has been shown that entropy at finer time scales increases while entropy at coarser time scales decreases with increasing age (McIntosh et al, 2014), which is in regard to our observations, plausible as fluid intelligence decreases with increasing age (Schaie, 1994;Salthouse, 2010;Ghisletta et al, 2012).…”
Section: Discussionsupporting
confidence: 86%
“…Microstate A has been related to reduced activity of the temporal network (Michel and Koenig, 2018) and especially to areas implicated in phonological processing (Britz et al, 2010), which is consistent with the observation that Microstate A is more present during visualization tasks expectedly implying inhibition of left-hemispheric language areas (Milz et al, 2016). However, implications of microstate patterns on cognition are far away from being completely understood and more research is needed to clarify whether and to which extend a higher presence of microstates A may possibly reflect intrinsic dispositions for verbal processing (Dreszer et al, 2020) or visualization (Milz et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations